Маленькая ведьма: [повесть] / Мэри Стюарт - Стюарт Мэри (Любимые книги девочек, 2001)
Экземпляры: С/а ДБ (20140724) / Инвентарный номер: 101321 / Цена: 30.00 / Авт.знак: С 88 / ГРНТИ: 17.82 / ББК: 84(4Вел)